Meningkatkan Aktivitas, Keterampilan Berpikir Kritis, Komunikasi, dan Hasil Belajar Siswa pada Mata Pelajaran Bahasa Indonesia Menggunakan Model GEMINTANG Kelas IV SDN Kuin Selatan 4 Banjarmasin - Salwa Salsabil Nur Aripin; Aslamiah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was motivated by the low levels of learning activity, critical thinking skills, communication skills, and learning outcomes in Indonesian language learning among fourth-grade students at SDN Kuin Selatan 4 Banjarmasin. These conditions limited students' active engagement in constructing knowledge, expressing ideas logically, collaborating with peers, and achieving optimal learning outcomes. This problem highlights the need for an innovative, student-centered learning model that integrates critical thinking, communication, and problem-solving into the learning process. The study aimed to describe teacher activities and analyze the improvement of students' learning activities, critical thinking skills, communication skills, and learning outcomes through the implementation of the GEMINTANG model, which integrates Problem Based Learning, Role Playing, and Talking Stick. This study employed Classroom Action Research conducted over four meetings involving 18 fourth-grade students. Data were collected through classroom observations and learning achievement tests. The findings revealed that teacher activity improved from a score of 25 to 32, student learning activity increased from 17% to 89%, critical thinking skills improved from 17% to 83%, communication skills increased from 22% to 83%, and classical learning mastery improved from 22% to 83%. These findings indicate that the GEMINTANG model effectively creates an active, collaborative, communicative, and meaningful Indonesian language learning environment, thereby improving students' learning activities, critical thinking skills, communication skills, and learning outcomes.